2011
DOI: 10.1002/ajh.22019
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to Imatinib adversely affects event free survival in chronic phase chronic myeloid leukemia

Abstract: There is limited data on the impact of treatment interruptions due to nonadherence in patients with chronic phase chronic myeloid leukemia (CP-CML) treated with Imatinib. We looked at factors (including adherence to therapy) affecting the outcome in a large cohort of patients with CP-CML. All the 516 patients received Imatinib free-of-cost through a company sponsored scheme, which mandated regular three monthly visits for drug procurement. Data regarding the disease characteristics, adherence to treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
166
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 13 publications
2
166
1
1
Order By: Relevance
“…Eight publications came from Europe, 14,15,18,19,21,24,25,30 5 from the US, 20,23,[31][32][33] 5 from Asia 22,26,28,29,35 and one from Australia.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight publications came from Europe, 14,15,18,19,21,24,25,30 5 from the US, 20,23,[31][32][33] 5 from Asia 22,26,28,29,35 and one from Australia.…”
Section: Literature Searchmentioning
confidence: 99%
“…An overview of the included articles is given in Online Supplementary Table S3. 14,15, Only 19 peer review articles were analyzed and reported in the Results section.Eight publications came from Europe, 14,15,18,19,21,24,25,30 5 from the US, 20,23,[31][32][33] 5 from Asia 22,26,28,29,35 and one from Australia.27 Almost half of the included studies were retrospective (9 of 19) and mainly conducted in the US and Asia 38,41,42,45,49,52,53 while half of the European studies were prospective (4 of 8). 14,15,18,24 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a third study, performed at the Adyar Cancer Institute, Chennai, India, has been reported in the literature [20]. The authors evaluated the records of 516 patients receiving imatinib for chronic-phase CML for adherence to therapy and patient outcomes.…”
Section: Impact Of Poor Adherence On Treatment Responsementioning
confidence: 99%